An Economic Evaluation of Voriconazole versus Amphotericin B for the Treatment of Invasive Aspergillosis in Canada - Coleman Rotstein; Michel Laverdière; Anne Marciniak; Farzad Ali (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Invasive aspergillosis (IA) is a serious fungal infection that affects immunocompromised patients. The Global Comparative Aspergillosis study demonstrated that voriconazole, a new broad-spectrum triazole, had better responses and improved survival compared with conventional amphotericin B deoxycholate (CAB) and other licensed antifungal therapy (OLAT) for the treatment of definite or probable aspergillosis.